2015
DOI: 10.1002/cnm.2707
|View full text |Cite
|
Sign up to set email alerts
|

Rational macromodeling of 1D blood flow in the human cardiovascular system

Abstract: In this paper, we present a novel rational macromodeling approach for the description of 1D blood flow in the human cardiovascular system, which is suitable for time-domain simulations. Using the analogy of the blood flow propagation problem with transmission lines and considering the hypothesis of linearized Navier-Stokes equations, a frequency-domain rational macromodel for each arterial segment has been built. The poles and the residues of each arterial segment macromodel have been calculated by means of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Pressure and flow waveform predictions delivered by this kind of models have been shown to compare satisfactorily with measurements for in-vitro models [1,2] and for patient-specific settings [3][4][5]. Relevant applications of one-dimensional models include the study of basic physiology [6][7][8][9][10][11][12], the study of pathological conditions [13], and the usage of these models as boundary conditions providers to more complex models [14][15][16][17][18], among many other applications.…”
Section: Introductionmentioning
confidence: 87%
“…Pressure and flow waveform predictions delivered by this kind of models have been shown to compare satisfactorily with measurements for in-vitro models [1,2] and for patient-specific settings [3][4][5]. Relevant applications of one-dimensional models include the study of basic physiology [6][7][8][9][10][11][12], the study of pathological conditions [13], and the usage of these models as boundary conditions providers to more complex models [14][15][16][17][18], among many other applications.…”
Section: Introductionmentioning
confidence: 87%
“…Experimental microfluidic studies have shown the influence of severe constrictions on a cell free layer of blood flow, blockage effects, the progress of infection to rigidity, and the attendant blockage . Although the mechanism behind the pathological conditions of i RBC is not well understood, its deformation dynamics at various stages of infection is certainly linked to the cell membrane stiffness, its aggregation dynamics, the transit velocity of the cells, microfluidic channel dimensions etc, where mathematical modeling would be very useful …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when the noninvasive measurements are difficult to obtain, 3D simulations cannot be performed. Alternatively, one powerful route is to perform a comprehensive lumped parameter OD modeling of the complete circulatory system to understand the hemodynamics . These models are based on the traditional electric circuit analogs and useful in tuning patient specific conditions of clinical interest .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent contribution, in this context, discusses the development of rational macro-models for one-dimensional blood flow in arteries (Ferranti et al, 2015). …”
Section: Introductionmentioning
confidence: 99%